PATU4 A population-based longitudinal study of cognitive and behavioural impairment in amyotrophic lateral sclerosis. Issue 11 (22nd October 2010) - Phukan, J; Hardiman, O; Jordan, N; Gallagher, L; Pender, N P
Abstract : Background: Up to 60% of people with ALS have mild cognitive decline; a smaller proportion develop frontotemporal dementia. The population-based frequency, clinical characteristics and natural history of cognitive decline in ALS are unknown. Objective: To determine the frequency and natural history of cognitive decline in ALS in a population-based cohort using the latest consensus criteria and an extensive neuropsychological battery. Results: Of 87 patients and matched controls, 32.2% had cognitive impairment (ALSci) at initial assessment. Memory deficits involved retrieval and retention, signalling more extensive temporal lobe involvement than previously recognised. Eight per cent had behavioural impairment (ALSbi); apathy was the most marked change. Total behavioural change predicted caregiver burden and mood. 18% met Neary criteria for frontotemporal dementia. Predictors for the development of dementia after 6 months included (1) baseline presence of cognitive impairment and (2) the presence of verbal fluency deficits. No patient with "pure" ALS (i.e., no cognitive or behavioural impairment) developed FTD. Conversely, 50% of patients with ALSci and 63% of those with ALSbi progressed to dementia. Conclusion/relevance: ALS is associated with a high prevalence of cognitive and behavioural change. The consensus guidelines facilitated categorisation of subgroups to track the evolution of cognitive and behavioural impairment over time but more rigorous validation is required prior their use in clinical practice. Those with normal cognitive function at baseline are less likely to develop dementia. Longitudinal studies are ongoing to confirm or refute whether ALS with cognitive impairment represents a distinct subpopulation of ALS or instead a continuum.